Housing integration of immigrants from Bosnia and Herzegovina in Croatia: example of the City of Zagreb - Sonja Podgorelec; Sanja Klempić Bogadi; Margareta Gregurović (Geoadria, 2020)
This paper analyses the results of the research on housing integration as the important part of functional integration of most numerous immigrant group in Croatia – Croatian citizens who were born in Bosnia and Herzegovina. The analysed survey (CAPI) was conducted in 2014 in Sesvete, a district in the City of Zagreb, on a judgemental/purposive sample of 301 respondents. The aim of the paper is to analyse objective housing conditions (home ownership, housing quality, and neighbourhood) and subjective assessments of the indicators of housing integration of immigrants from BiH living in one of City of Zagreb. Mostly descriptive analyses were employed, complemented with selected tests of relations between two or more respondents’ characteristics and their estimations of housing standard and quality. While deriving conclusions from the obtained results, special attention was attached to the limitations of the sampling methods and specific characteristics of the target population of immigrants from BiH. Depending on the ethnic affiliation of immigrants, their language, history and cultural tradition are identical (for Croats) or very similar (Serbs and Bosniaks) to the majority population in the host country creating the circumstances and characteristics which make the process of integration easier in all of its aspects. The analysed indicators of housing integration and development of housing quality of immigrants included in the survey confirmed a high level of its successfulness. In all characteristics of housing: home ownership, type of dwelling (house or apartment) and infrastructural facilities, the immigrants from BiH do not differ from the total population of Croatia, while they are above average in size of total living area and number of rooms. Significant differences were obtained in regard to period and main reason of migration to Croatia. The analysis of comparative estimation of housing quality and general life standard in Zagreb in 2014 and in BiH in the period of migration showed that significant proportion of respondents (57%) considers their housing and living standard in Croatia to be better than if they stayed in BiH.